Propuesta de logística inversa para el aprovechamiento de tapabocas desechables en la elaboración de prótesis (2023)
This research project focuses on the importance of taking advantage of the face mask in the country, in order to minimize the environmental impacts and the diseases generated by the and diseases generated by the improper final disposal of such waste. For this reason, information was collected in order to identify the different ways in which this protective element can be of this protective element to elaborate a variety of by-products such as flower pots, glasses, etc. Upon evidencing these ideas, the proposal to make a part of the prosthesis called socket to help mitigate the high pollution caused by the plastics industry in the world is contemplated. This proposal consists of taking advantage of the face mask to produce the socket of a prosthesis in Colombia. For its development, a diagnosis of the current situation of plastics, specifically the the current situation of the plastics industry, specifically of the face mask, in order to determine how people discarded and the perception that people have about the environmental impact. Afterwards, the types of mouthpiece were identified and classified, the type of face mask, the type of disinfection, the type of recycling to be carried out, and the method of transportation of the mask. Taking into account the above, the steps to be followed to develop a correct reverse logistics, including storage, transportation, among other factors, were structured.